Strategic Development of Piezoelectric Nanogenerator and Biomedical Applications - Omkar Y. Pawar; Snehal L. Patil; Rahul S. Redekar; Sharad B. Patil; Sooman Lim; Nilesh L. Tarwal (Applied Sciences, 2023)
Nanogenerators are the backbone of self-powered systems and they have been explored for application in miniaturized biomedical devices, such as pacemakers. Piezoelectric nanogenerators (PENGs) have several advantages, including their high efficiency, low cost, and facile fabrication processes, which have made them one of the most promising nano power sources for converting mechanical energy into electrical energy. In this study, we review the recent major progress in the field of PENGs. Various approaches, such as morphology tuning, doping, and compositing active materials, which have been explored to improve the efficiency of PENGs, are discussed in depth. Major emphasis is given to material tailoring strategies and PENG fabrication approaches, such as 3D printing, and their applications in the biomedical field. Moreover, hybrid nanogenerators (HNG), which have evolved over the last few years, are discussed. Finally, the current key challenges and future directions in this field are presented.